Cross-National Estimates of the Intergenerational Mobility in Earnings - Dean R. Lillard (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
This paper examines the similarity in the association between earnings of sons and fathers in Germany and the United States. It relaxes the log-linear functional form imposed in most studies of the intergenerational earnings association. Theory implies the relationship between earnings of fathers and sons could be nonlinear, especially at the tails of the distribution of earnings of fathers. When a more flexible function form is fit to the data, the apparent similarity between Germany and the United States disappears. Relative to mobility in Germany, upward mobility is higher in the United States for sons with the poorest fathers and downward mobility is lower for sons with fathers with high earnings.
Keywords: 330; Einkommen; Kinder; Soziale Mobilität; Generationengerechtigkeit; Vergleich; Deutschland; USA; Eltern